Proporsi Volume Ekstrak Belimbing Wuluh Terhadap Sifat Organoleptik Hair Tonic - Wilujeng, Biyan Yesi; Wijaya, Nieke (Journal of Beauty and Cosmetology (JBC), 2019)
Dandruff is an excessive exfoliation of dead skin cells on the scalp. The effect of dandruff is itching and even inflammation, so it can interfere with concentration when doing activities. One of the many examples of the beauty world response to the dandruff problem is the emergence of products in the form of anti-dandruff shampoo on the market. The purpose of this study was to determine the results of the organoleptic hair tonic of ˜Averrhoa billimbi L extract. Organoleptic test results showed that H3 has the highest average value in the aspects of color, scent, homogeneity and impression on the skin. Keywords: hair tonic, organoleptic, starfruit